PARAMETERS DERIVED FROM RESERVOIR PRESSURE ANALYSIS INDEPENDENTLY PREDICT CARDIOVASCULAR EVENTS IN A MULTI-CENTRE STUDY OF INDIVIDUALS WITH TYPE 2 DIABETES. (June 2018) - Aizawa, K.; Casanova, F.; Mawson, D.M.; Gooding, K.M.; Strain, W.D.; Gates, P.E.; Östling, G.; Nilsson, J.; Khan, F.; Colhoun, H.M.; Palombo, C.; Parker, K.H.; et al.
Abstract : Objective: Central haemodynamic parameters derived from reservoir pressure analysis (RPA) possess prognostic utility in several populations. However, evidence in type 2 diabetes (T2DM) remains scarce. We determined if these parameters would be associated with T2DM, and whether they would predict cardiovascular events in individuals with T2DM. Design and method: We studied 313 T2DM individuals with CVD (DMCVD: 70.5 ± 7.9yrs, 96F), 367 T2DM individuals without CVD (DM: 67.7 ± 8.3yrs, 148F) and 185 individuals without T2DM or CVD (CONT: 67.1 ± 8.8yrs, 88F). RPA-derived parameters including reservoir pressure integral (INTPR), peak reservoir pressure (MAXPR), excess pressure integral (INTXSP), systolic rate constant (SRC) and diastolic rate constant (DRC) were obtained by radial artery tonometry. Results: Parameters of RPA stratified by group are presented in the Table. INTPR was lower in DMCVD and DM than CONT. MAXPR and SRC were lower, and INTXSP was greater in DMCVD compared to DM and CONT. DRC was greater in DMCVD than CONT. In a subgroup of individuals with T2DM (n = 666, 69.1 ± 8.2yrs, 237F, 308CVD), 14 deaths (6 cardiovascular and 8 non-cardiovascular causes) and 104 cardiovascular events occurred during a 3-yr follow-up period. Although baseline clinical characteristics of individuals who experienced a cardiovascular event (n = 85) and those who did not (n = 581) were similar, INTPR (83.0 ± 16.2 vs 87.6 ± 16.6 mmHg s) was lower, and INTXSP [7.5(6.5–9.8) vs 7.3(5.8–9.1) mmHg s] and DRC [2.7(2.1–3.2) vs 2.4(1.9–2.9) s-1] were greater at baseline in individuals who had cardiovascular events than those without (all p < 0.05). Logistic regression analysis revealed that INTPR and DRC were independent predictors of cardiovascular events during follow-up after adjusting for conventional risk factors [INTPR, odds ratio 0.97 (95%CI: 0.95–0.99); DRC, odds ratio 4.95 (95%CI: 2.10–11.65)]. Further adjustments for body mass index, renal function, T2DM duration or previous CVD history had no substantial influence on associations. Conclusions: These findings demonstrate that altered RPA-derived parameters are associated with T2DM. Furthermore, baseline values of INTPR and DRC independently predict cardiovascular events in individuals with T2DM, indicating a potential clinical utility of these parameters for risk stratification in T2DM. Figure. No caption available.